Analisis Kompetensi Guru SMA Selama Pembelajaran Daring di Masa Pandemi Covid-19 - Sutrisno; Nur Amaliah; Yusrianto Nasir (BIOMA: Jurnal Biologi dan Pembelajarannya, 2023)
This study aims to determine the competency of high school teachers in online learning during the COVID-19 pandemic. This study was a qualitative approach by using data of interviews, teacher competency questionnaires, and relevant documents. The study design was a case study by investigating problems related to the teaching competence of high school teachers in Majene Regency. The technique of data validity were credibility, transferability, dependability, and confirmability tests. The technique of data analysis consists of data reduction, data display, and drawing conclusions. The results of this study showed that the competency of high school teachers in Majene Regency during online learning during the COVID-19 pandemic was good.